The application of big data and advanced modelling techniques in dairy cattle lameness research - Thomas, Matthew (2024)
The impact of lameness on animal welfare and productivity is a significant concern in dairy farming. Claw Horn Disruption Lesions (CHDLs) are the leading cause of lameness however significant gaps exist in our current understanding of their temporal risk relation, detection, and behavioural implications. The availability of long-term, large-scale datasets combined with the effective use of emerging technologies, particularly sensors for behavioural classification, enables a more confident expansion on the current literature and a deeper exploration.